Educational intervention program for oral health in elderly people - Teresita de Jesús Barrio Pedraza; Nora Sexto Delgado; Esther Victoria Barrio Pedraza; Alicia Maria Quiñones Betancourt (Medisur)
Background: The creation of educational intervention programs for oral health in elderly people contributes to the development of positive behaviours towards oral health in this age group. Objective: To elaborate an educational intervention program aimed at raising the knowledge level related with oral-dental health. Method: An interventional, cuasi-experimental study was developed with before-after design for people from the University Group of the Elderly, sponsored by Cienfuegos Health Palace from January 2007 to May 2008. The information was collected through surveys, focal groups, experts´ opinions and observation. The changes produced by the following markers were assessed: absolute numbers, percentages and the Mac Nemar test. The educational intervention program with educative and affective techniques was applied, combined with didactic games as feedback. The studied variables were: age group, brushing frequency and form, use of dental floss and removable bridges and the relation of diet with oral diseases. Qualitative methods showed audience approval towards the used strategy. Results: 44 elderly people were studied with a prevalence of incorrect brushing, incorrect oral hygiene and inappropriate use of dental floss. 97, 7% had incorrect knowledge about use and maintenance of the prosthesis and 100% developed abilities for oral self-examination. Conclusions: The educative intervention program allowed elderly people learning self-care actions leading to the improvement of their oral health.